Vendor Selection for Subcontracted Greige Fabric A Case Study of PT X - Sherli Dwi Setiawati; Eka Ludiya (LP2M IAIN Palopo, 2026)
The limitations of internal production capacity, especially in textile companies, resulted in the company having to implement a greige fabric subcontracting strategy to meet the company's needs. The purpose of this study was to analyze planning, implementation, and evaluation, as well as to analyze improvement efforts in selecting subcontracting vendors using the Analytical Hierarchy Process (AHP) method and assisted by Expert Choice software. The research method used was qualitative with data collection techniques through interviews, observations, and documentation. This study used a purposive sampling technique, and the criteria used in vendor selection were price, quality, delivery accuracy, and quantity accuracy. The results showed that the first priority performance vendor was Cemara vendor with a weight of 41.4% (MS.Excel Processing) 41.4% (Expert Choice Processing), priority 2 was Ajutex vendor with a weight of 32.5% (MS.Excel Processing) 33.1% (Expert Choice Processing), and priority 3 was Daese vendor 26.1% (MS.Excel Processing) 25.5% (Expert Choice Processing). So it can be concluded that the best vendor recommendation for PT. X is Cemara, because Cemara has the highest priority value.